2007
DOI: 10.1007/s00468-007-0142-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation of δ13C of larch leaves from a montane boreal forest in Mongolia

Abstract: This paper reports the temporal variation (2002)(2003)(2004) in foliar d 13 C values, which are indicative of long-term integrated photosynthetic and water use characteristics, of Siberian larch (Larix sibirica Ledeb.) trees in a montane forest at Mongonmorit, NE Mongolia. At the stand, the d 13 C value for understory shaded leaves was more negative by 2& on average than that for sunlit leaves sampled concurrently from open and sun-exposed environments in a forest gap. The d 13 C value of both sunlit and shade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 72 publications
(98 reference statements)
4
54
2
Order By: Relevance
“…The highest concentrations of foliar N, P, and K at all permafrost-affected sites were found in the early growing season, when the needles were first produced. A similar pattern was reported for the same elements in Siberian larch from Mongolia [9] and micronutrients (i.e., Cu, B, Na, Ni etc.) in the same habitats for Gmelin's larch [32].…”
Section: Strong Seasonal Dynamics In Nutrient Concentrations and 13 Csupporting
confidence: 51%
See 3 more Smart Citations
“…The highest concentrations of foliar N, P, and K at all permafrost-affected sites were found in the early growing season, when the needles were first produced. A similar pattern was reported for the same elements in Siberian larch from Mongolia [9] and micronutrients (i.e., Cu, B, Na, Ni etc.) in the same habitats for Gmelin's larch [32].…”
Section: Strong Seasonal Dynamics In Nutrient Concentrations and 13 Csupporting
confidence: 51%
“…in the mid-growing season observed in this study are in the lower range of reported values for Eurasia and Northern America [5,9,13,26] (Figure 6). At the permafrost site at Tura, concentrations of N, P, and K in mature needles were 50% less than the optimum contents of major nutrients in larch needles (2.1-2.6% for N, 0.3-0.6% for P, and 0.9-2.0% for K) reported by [13].…”
Section: Nutrient Status Of Larch Improves With Active Layer Depthcontrasting
confidence: 42%
See 2 more Smart Citations
“…SKT is a Siberian larch (Larix sibirica) forest located at approximately 25 km northeast of the Mongonmorit village in the Tov province of Mongolia (Li et al, 2005(Li et al, , 2006(Li et al, , 2007. The age structure of the larch ranged from ∼ 70 to over 150 years old, but the oldest trees were older than 300 years.…”
Section: Site Descriptionsmentioning
confidence: 99%